2014
DOI: 10.5846/stxb201212051752
|View full text |Cite
|
Sign up to set email alerts
|

Source areas and landing mechanisms of early immigrant population of white-backed planthoppers Sogatella furcifera (Horváth) in Shizong, Yunnan Province

Abstract: From April to May, 1990-2012, the source areas of early immigration of white鄄backed planthoppers Sogatella furcifera (Horv佗th) (WBPH) were studied through the analysis on the daily light鄄trap catches, immigration trajectory simulation and horizontal wind field. The following results were obtained: The high frequency of westerly wind carried the large population of WBPH to Shizong in late April. The source areas were mainly located in northeastern Myanmar and the secondary source areas were at northern Vietnam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The white‐backed planthopper (WBPH), Sogatella furcifera (Horváth) (Hemiptera: Delephacidae), is one of the most destructive rice pests throughout South and East Asia (Otuka, 2013). It is an oligophagous insect and has high fecundity and long‐distance flight capabilities (Zheng et al., 2014). The adults and nymphs of WBPH not only directly injure rice plants by sap‐sucking and ovipositing in rice tissues, weakening plant vigor, delaying tillering, stunting, yellow leaves and shrivelling grain but also cause further damage by transmitting the southern rice black‐streaked dwarf virus (SRBSDV) (Su et al., 2013; Zhou et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The white‐backed planthopper (WBPH), Sogatella furcifera (Horváth) (Hemiptera: Delephacidae), is one of the most destructive rice pests throughout South and East Asia (Otuka, 2013). It is an oligophagous insect and has high fecundity and long‐distance flight capabilities (Zheng et al., 2014). The adults and nymphs of WBPH not only directly injure rice plants by sap‐sucking and ovipositing in rice tissues, weakening plant vigor, delaying tillering, stunting, yellow leaves and shrivelling grain but also cause further damage by transmitting the southern rice black‐streaked dwarf virus (SRBSDV) (Su et al., 2013; Zhou et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, by mid-May, it is confirmed that the main source of these migrating insects is the northern regions of Vietnam. This migration process is, to some extent, influenced by the seasons and climate, forming an organized and sustained migration chain [15,17]. Despite some evidence based on molecular marker analysis [18,19], our understanding of the genetic flow and migration patterns of the WBPH between Myanmar and Yunnan Province, China remains limited.…”
Section: Introductionmentioning
confidence: 99%